Reduced Dopamine Transporter Expression in the Amygdala of Subjects Diagnosed With Schizophrenia - Markota, Matej (Oxford University Press, 2014)
A disruption of dopaminergic transmission in the amygdala of subjects with schizophrenia was proposed as a main contributor to pathophysiological and clinical manifestations of this disorder. We tested the hypothesis that the expression of the dopamine transporter (DAT) is decreased in the amygdala of subjects with schizophrenia. In normal control, schizophrenic subjects and bipolar disorder subjects, we measured numerical density of axon varicosities immunoreactive (IR) for DAT in the lateral (LN), basal, accessory basal (ABN), and cortical (CO) nuclei and intercalated cell masses (ITCM) of the amygdala. Tyrosine hydroxylase (TH)-IR and dopamine beta-hydroxylase (DBH)-IR varicosities were measured to test for potential loss of varicosities and serotonin transporter (5HTT)-IR for involvement of the serotoninergic system. Among several potential confounding variables tested, particular emphasis was placed on exposure to therapeutic drugs. In schizophrenic subjects, DAT-IR varicosities were decreased in LN (P = .0002), ABN (P = .013), and CO (P = .0001) in comparison with controls, and in comparison with bipolar disorder subjects in LN (P = .004) and CO (P = .002). DBH-IR varicosities were decreased in ABN (P = .008) and ITCM (P = .017), compared with controls. TH- and 5HTT-IR varicosities were not altered. No changes were detected in bipolar disorder. Taken together with TH and DBH findings, reductions of DAT-IR varicosities point to decreased DAT expression in dopaminergic terminals in the amygdala of subjects with schizophrenia. This DAT decrease may disrupt dopamine uptake, leading to increased dopaminergic synaptic transmission and spillage into the extracellular space with activation of extrasynaptic dopamine receptors. Concurrent decrease of noradrenaline in the ABN may disrupt memory consolidation.